Examination of Barcode Designs as an Aesthetic Graphic Design Product - Yücelen, Bora Bekir; Mercin, Levent (Istanbul Medeniyet University, 2024)
Rapid consumption habits have led to a significant increase in the number of companies across the sector and the variety of processed foods. This has led to a significant increase in the variety of packaged products. In order to differentiate their products from others and make them stand out, companies need to enrich the attributes of their products, conduct advertising campaigns, or make their packaging designs more attractive. Therefore, companies prefer to use visual and typographic compositions in their packaging designs to highlight the features that distinguish their products from their counterparts and increase their recognizability. One of these visuals is barcodes. Although the primary purpose of the barcode as a graphic symbol on the packaging is to provide information and communication, it can also become a visual image that complements other visuals on the packaging surface and adds aesthetic value. This study investigated whether barcodes are a functional graphic symbol in packaging designs, whether they can also take place as an aesthetic image, and whether they are an element that complements the integrity of packaging design and adds value to it. The research used general survey models, a review of the relevant literature, and artifact analysis methods. According to the data obtained, when the designs in which barcodes stand out as an aesthetic element are examined, it is observed that the designs are generally based on the form of the packaging, the position of the shapes and images used on the packaging, the value of the colors and lines on the surface, and are mainly composed of lines and numbers. In our age where the use of visual elements in the field of communication is inevitable, it can be said that both packaging design and barcode designs as art objects enrich the aesthetic perception of society and reflect a different visual heritage to the world of art and design beyond its original purpose and function.

Hızlı tüketim alışkanlıkları, işlenebilir gıda çeşitlerinin artmasıyla birlikte, sektör genelinde firma sayısında belirgin bir artışa yol açmıştır. Bu artış, ambalajlı ürünlerin çeşitliliğinde belirgin bir yükselişe sebep olmuştur. Firmalar, ürünlerini diğerlerinden ayırt edilmesini sağlamak ve öne çıkartmak için ürünlerin nitelikleriyle ilgili özelliklerini zenginleştirmeye, reklam kampanyaları yapmaya veya ambalaj tasarımlarını daha dikkat çekici hale getirmeye ihtiyaç duymaktadır. Bu yüzden, firmalar ürünlerini benzerlerinden ayıran özelliklerini öne çıkartmak ve fark edilebilirliğini artırmak amacıyla, ambalaj tasarımlarında görsel ve tipografik kompozisyonlar kullanmayı tercih etmektedir. Bu görsellerden biri de barkodlardır. Bir grafik simge olarak barkodun ambalaj üzerindeki asıl amacı bilgi ve iletişim kurmak olsa da ambalaj yüzeyindeki diğer görselleri tamamlayan ve estetik değer katan birer görsel imgeye de dönüşebilmektedir. Bu çalışmada, barkodların ambalaj tasarımlarında işlevsel bir grafik simge olup olmadığı, aynı zamanda estetik bir imge olarak da yer alıp alamayacağı; ambalaj tasarım bütünlüğünü tamamlama ve ona değer katan bir unsur olup olmadığı araştırılmıştır. Araştırmada genel tarama modellerinden ilgili literatürün taranması ve eser analizi yöntemlerinden yararlanılmıştır. Elde edilen verilere göre barkodların estetik bir unsur olarak öne çıktığı tasarımlar incelendiğinde, tasarımların genel olarak ambalajın formuna, ambalaj üzerinde kullanılan şekil ve imgelerin konumuna, yüzeydeki renk ve çizgilerin değerine kurgulanmış ve çoğunlukla çizgi ve rakamlardan oluşan bir anlayış ile ortaya kondukları gözlemlenmiştir. Görsel unsurların iletişim alanında kullanımının kaçınılmaz olduğu çağımızda gerek ambalaj tasarımı gerek sanat nesnesi olarak barkod tasarımlarının, toplumun estetik algısını zenginleştirerek, asıl amaç ve işlevinin ötesinde sanat ve tasarım dünyasına farklı bir görsel miras olarak yansıdığı söylenebilmektedir.
Estetik Bir Grafik Tasarım Ürünü Olarak Barkod Tasarımlarının İncelenmesi
Keywords: Graphic Design; Grafik Tasarımı